2013
DOI: 10.1175/jas-d-12-052.1
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Composite Dropsonde Profiles for Developing and Nondeveloping Tropical Waves during the 2010 PREDICT Field Campaign

Abstract: Composite dropsonde profiles are analyzed for developing and nondeveloping tropical waves in an attempt to improve the understanding of tropical cyclogenesis. These tropical waves were sampled by 25 reconnaissance missions during the 2010 Pre-Depression Investigation of Cloud-Systems in the Tropics (PREDICT) field campaign. Comparisons are made between mean profiles of temperature, mixing ratio, relative humidity, radial and tangential winds, relative vorticity, and virtual convective available potential energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…It is known, however, that TCs also develop in environments with moderate to strong deep-layer vertical wind shear (e.g., Bracken and Bosart 2000;Davis and Bosart 2001, 2002, 2003 and over relatively cool SSTs (e.g., McTaggart-Cowan et al 2006). In fact, previous research has demonstrated that half of all TC developments over the North Atlantic occur in environments with moderate to strong baroclinicity and attendant vertical wind shear (e.g., McTaggart-Cowan et al 2008, 2013Hess et al 1995;Elsner et al 1996). These baroclinically influenced TC developments encompass subtropical cyclones that undergo tropical transition (TT; e.g., Bosart 2003, 2004;Evans and Guishard 2009;Guishard et al 2009;Hulme and Martin 2009a,b) and precursor low-level cyclonic vorticity centers that interact with upper-tropospheric troughs (e.g., Sadler 1976Sadler , 1978Lander 1994;Molinari et al 1995;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is known, however, that TCs also develop in environments with moderate to strong deep-layer vertical wind shear (e.g., Bracken and Bosart 2000;Davis and Bosart 2001, 2002, 2003 and over relatively cool SSTs (e.g., McTaggart-Cowan et al 2006). In fact, previous research has demonstrated that half of all TC developments over the North Atlantic occur in environments with moderate to strong baroclinicity and attendant vertical wind shear (e.g., McTaggart-Cowan et al 2008, 2013Hess et al 1995;Elsner et al 1996). These baroclinically influenced TC developments encompass subtropical cyclones that undergo tropical transition (TT; e.g., Bosart 2003, 2004;Evans and Guishard 2009;Guishard et al 2009;Hulme and Martin 2009a,b) and precursor low-level cyclonic vorticity centers that interact with upper-tropospheric troughs (e.g., Sadler 1976Sadler , 1978Lander 1994;Molinari et al 1995;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, smaller-scale thermodynamics and TC internal dynamics also play an important role in TC genesis (e.g., Simpson et al 1997;Raymond and Sessions 2007;Wang 2012;Smith and Montgomery 2012;Komaromi 2013) and thus modulate TC counts. On the other hand, TC tracks are primarily determined by environmental steering flows with a relatively smaller contribution from the interaction between TC dynamics and the steering flow (e.g., George and Gray 1976;Holland 1983).…”
Section: Introductionmentioning
confidence: 99%
“…A trajectory analysis (not shown) indicates that the majority of the midlevel low-u e air to the north of TCS025 during IOP-2 originated from the TUTT cell that was originally to the east of TCS025. According to Komaromi (2013), the impact of midlevel low-u e air on storm development may be greater than low-u e air in the lower troposphere. Therefore, although vertical wind shear weakened when the TUTT cell was north of TCS025, the presence of low-u e air in the surrounding environment appears to have offset the positive impact of reduced vertical wind shear.…”
Section: Discussionmentioning
confidence: 99%
“…Komaromi (2013) found that nondeveloping systems were on average 10%-20% drier between 500 and 700 hPa than the mean, but were actually moister in the low levels. Komaromi (2013) suggested that midlevel dry air may have a larger negative impact on storm formation (through convective entrainment) compared to dry air in the low levels.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation